Global integration and growth in Honduras and Nicaragua - Manuel R. Agosin (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
This paper discusses the experience with opening up to the global economy of two small Central American countries, Honduras and Nicaragua. They have both strengthened democratic processes and reduced defence expenditure dramatically. Both have liberalized their trade régimes in the context of regional integration within Central America and have encouraged foreign direct investment and investment in export processing zones. Nicaragua has made considerable progress toward macroeconomic stability. Honduras, on the other hand, has taken significant strides toward changing its pattern of exports toward more sophisticated primary-product based goods and simple manufactures. In addition, Honduras has emerged as a major assembler of clothing for the United States market. However, neither country has yet succeeded in launching rapid, export-oriented growth. Some of the reasons are weak linkages between the export sector and the rest of the economy, ambiguous signals to private sector producers emanating from economic policy, and low levels of labour productivity. Improving the latter will require major investments in human resources, mainly in education and health. – globalization ; Latin America and the Caribbean ; sustainable growth
Keywords: F13; F43; O54; 330; Wirtschaftswachstum; Wirtschaftliche Anpassung; Honduras; Nicaragua